Temporary disability pension recipients: Contextual stress factors and their effect on return-to-work-intention - Savvoulidou, Dimitra; Kröger, Christoph; Kobelt-Pönicke, Axel (Die Rehabilitation, 2024)
Background and purpose In the last decades, Germany has experienced a vast increase in the number of individuals applying for or receiving disability benefit. Only a small proportion of them intends to return to work. The present study aims to identify and describe the percentage of temporary disability pensioners, who have the intention to return to working life.Methods The final sample consisted of 496 insured individuals who were receiving temporary disability pension from the Regional German Pension Insurance (DRV) at that time. Participation was voluntary and anonymous. The following self-report instruments were administered: a. Evaluation of Contextual Factors; b. German Symptom Validation Test (BEVA); c. German Patient Health Questionnaire (PHQ-9); d. Readiness for Return-to-Work German Scale (RRTW).Results The results revealed that approximately 6% of participants were at the stage of “preparation”, 31.9% at the stage of “contemplation”, and more than half of the participants were at the stage of “pre-contemplation” according to the RRTW. Comparing the groups of “pre-contemplation” (Group 1) and “contemplation+preparation” (Group 2+3), no statistically significant differences were found, except for age.Conclusions In conclusion, further research is required to identify possible factors which could predict the stage of RRTW. New interventions are needed that can raise the motivation for and success in the return to work of disability pensioners.
Keywords: Disability pension; Return to Work; Contextual factors; BEVA; PHQ-9